2024
DOI: 10.1111/cpr.13602
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient metabolism in regulating intestinal stem cell homeostasis

Ruicheng Shi,
Bo Wang

Abstract: Intestinal stem cells (ISCs) are known for their remarkable proliferative capacity, making them one of the most active cell populations in the body. However, a high turnover rate of intestinal epithelium raises the likelihood of dysregulated homeostasis, which is known to cause various diseases, including cancer. Maintaining precise control over the homeostasis of ISCs is crucial to preserve the intestinal epithelium's integrity during homeostasis or stressed conditions. Recent research has indicated that nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Intestinal stem cells, for example, have been observed to have a higher pyruvate-to-lactate ratio and respiration rate compared to Paneth cells. Recently the role of nutrients and metabolic pathways has shown that they can have a significant impact on intestinal LGR5 cells, but the mechanism is not yet understood ( Shi and Wang, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal stem cells, for example, have been observed to have a higher pyruvate-to-lactate ratio and respiration rate compared to Paneth cells. Recently the role of nutrients and metabolic pathways has shown that they can have a significant impact on intestinal LGR5 cells, but the mechanism is not yet understood ( Shi and Wang, 2024 ).…”
Section: Introductionmentioning
confidence: 99%